Effects of dietary fish oil supplementation on the skeletal muscle blood flow response to submaximal treadmill exercise - Hammel, Lauren E. (Kansas State University, 2008)
Dietary supplementation with omega-3 polyunsaturated fatty acids (PUFAs) containing docosahexaenoic (DHA) and eicosapentaenoic acid (EPA) has been demonstrated to produce advantageous effects on vascular function. Specifically, PUFA supplementation has resulted in enhanced brachial artery blood flow (Q), dilation, and vascular conductance (VC) during rhythmic handgrip exercise. The effects of fish oils (FO) on skeletal muscle blood flow (Qm) during dynamic whole body exercise, however, remain unknown. PURPOSE: To test our hypothesis that 6 weeks of dietary FO supplementation with DHA and EPA enhances regional Qm and VC to the hindlimb musculature during submaximal treadmill exercise. METHODS: Following 6 weeks of dietary supplementation with safflower oil (SO) (control; n = 9) or FO (n = 8), heart rate (HR), mean arterial pressure (MAP), and Q[subscript]m to the hindlimb were measured at rest and during submaximal treadmill exercise (20 m/min, 10%, ~65% VO[subscript]2max) via radiolabeled microspheres in adult male Sprague-Dawley rats. RESULTS: HR and MAP were not different between SO and FO at rest or exercise (P<0.05). Q[subscript]m and VC were not different between SO and FO at rest. During exercise, FO exhibited greater Q[subscript]m in 8 of the 28 muscle parts measured as well as greater VC in 11 of the 28 muscle parts measured. Additionally, FO exhibited greater (Q)[subscript] m (158[plus or minus]9) and VC (1.156[plus or minus]0.066) to the total hindlimb musculature than SO (128[plus or minus]10 ml/min/100g, 0.918[plus or minus]0.077 ml/min/100g/mmHg) (P<0.05). CONCLUSION: These results demonstrate that 6 weeks of dietary FO supplementation with DHA and EPA results in enhanced Q[subscript]m and VC to the hindlimb during submaximal exercise. Thus, supplementation with DHA and EPA may have therapeutic effects on oxygen delivery and vascular function in patients with impaired vascular function and exercise tolerance (i.e., congestive heart failure, diabetes).
Keywords: Blood flow; Fish oils; Skeletal muscle; Exercise; Radiolabeled microspheres; Biology, Animal Physiology (0433)